Expression of glutathione peroxidase 2 is associated with not only early hepatocarcinogenesis but also late stage metastasis - Shugo Suzuki (2018)
Understanding of mechanisms of cancer progression is very important for reduction of cancer mortality. Of six rat hepatocellular carcinoma (HCC) cell lines, differing in their metastatic potential to the lung after inoculation into the tail vein of nude mice, the most metastatic featured particular overexpression of glutathione peroxidase 2 (GPX2). Therefore, we analyzed the influence of interference in highly metastatic L2 cells by siRNA transfection. Gpx2 siRNA significantly inhibited cell proliferation at 24 and 48. h time points with induction of apoptosis but not cell cycle arrest. High expression of mutated p53 was detected in all HCC cell lines, with reduction in Gpx2 siRNA-transfected cells. Migration and invasion in vitro were also suppressed as compared to control siRNA-transfected cells and secretion of matrix metalloproteinase 9 was reduced. In vivo, the numbers and areas of metastatic nodules per area in the lungs were significantly reduced in the mice inoculated with Gpx2 siRNA-transfected cells as compared to control siRNA-transfected cells. In conclusion, expression of GPX2 is associated with cancer metastasis from rat HCCs both in vitro and in vivo. Together with immunohistochemical findings of elevated expression in rat and also human liver lesions, the results point to important roles in hepatocarcinogenesis. © 2013 Elsevier Ireland Ltd.